Massive use of tattoos and psychopathological clinical evidence - Perrotta, Giulio (Archives of Community Medicine and Public Health, 2021)
Purpose: This research aims to identify any recurrent psychopathological profiles in individuals who abuse tattoos and that, for this reason, the tattoo itself could be the manifestation of a specific symptom. Methods: Clinical interview and administration of the MMPI-II and PICI-1. Results: The research on a population sample of 444 people has shown a strong psychopathological tendency in the MMPI-II that is confirmed in the PICI-1 (TA version); in fact, the data are even more significant and expressive a precise psychopathological diagnosis of personality. In the male group with a percentage of less than 25%, at least three dysfunctional traits of anxiety, phobic, obsessive, somatic, borderline and antisocial disorder emerged individually. In the male group with a percentage between 26% and 50%, at least four dysfunctional traits of borderline, narcissistic, sadistic and masochistic disorder emerged individually. In the male group with a percentage between 51% and 75%, at least 5 dysfunctional traits of bipolar, borderline, narcissistic, antisocial, sadistic and masochistic disorder emerged individually. In the male group with a percentage between 76% and 100%, at least 6 dysfunctional traits of borderline, narcissistic, antisocial, sadistic and masochistic disorder emerged individually. In the female group with a percentage of less than 25%, at least three dysfunctional traits of anxiety, phobic, obsessive, somatic, borderline and bipolar disorder emerged individually. In the female group with a percentage between 26% and 50%, at least four dysfunctional traits of borderline, borderline, anxiety, phobic, obsessive, somatic, sadistic and masochistic disorder emerged individually. In the female group with a percentage between 51% and 75%, at least five dysfunctional traits of bipolar, borderline, narcissistic, antisocial, sadistic and masochistic disorder emerged individually. In the female group with a percentage between 76% and 100%, at least 6 dysfunctional traits of bipolar, borderline, narcissistic, antisocial, sadistic and masochistic disorder emerged individually. Conclusions: On the basis of these data, it is reasonable to argue that as the percentage of body surface area covered by tattoos increases, so do the dysfunctional traits of a specific main disorder. In particular, the recurrent dysfunctional traits are anxious, phobic, obsessive, somatic and bipolar in subjects with less than 25% of the body surface covered by tattoos, while borderline, narcissistic, antisocial, sadistic and masochistic traits are more frequent in subjects with more than 26% of the body surface covered by tattoos. Comparing the data with the control group we reasonably come to the conclusion that the use of tattoos is not directly related to the presence of one or more psychopathologies, but if the use is massive this is a fairly robust indicator of the likely presence of a significant number of psychopathological traits of the same morbid condition.